Factors associated with penalty outcome on male elite goalball - Furtado, O. L. P. d. C.; Häyrinen, M.; Alves, I. d. S.; Travitzki, L.; Morato, M. P. (Adapted Physical Activity Quarterly, 2023)
The authors` purpose was to examine the factors associated with penalty outcomes of male elite goalball. A total of 122 video-recorded matches from two Paralympic Games (i.e., 2012 and 2016) and the 2014 Goalball World Championship were assessed using notational analysis. Individual (n = 2), situational (n = 4), and performance variables (n = 7) were analyzed with good strength of agreement for intra- and interrater kappa index values. Their results showed that penalties play a very important role in the final score, composing around 25% of total goals in elite goalball matches. Winners were awarded on average with 62% of penalties and had 66% effectiveness compared with losers (31% and 53%) or drawers (8% and 52%). Based on the authors` findings, penalty takers should direct their throws at specific target sectors on the court, which could increase their rate of success to over 80%.